Ảnh hưởng của dung môi đến tính bền của xúc tác phức coban dị thể trong phản ứng oxi hóa chọn lọc của sec-phenetyl ancol - Thu Hà và cộng sự, Vũ Thị (Vietnam Journal of Chemistry, 2014)
In this work the effect of solvent and N-hydroxyphtalimide (NHPI) on the cobalt leaching and on the activity and the stability of silica based cobalt (II) interphase catalyst for aerobic oxidation of sec-phenethyl alcohol (a-methylbenzyl alcohol) was investigated. The solvents that were used in this work are CH3CN and CH3COOC2H5. It has been found that under similar reaction conditions, with CH3CN as solvent, the system consisting NHPI combined with Co/SBA-15 lead a sec-phenethyl alcohol conversion of 36.4% after 9 h of reaction while in the presence of CH3COOC2H5 as solvent, the sec-phenethyl alcohol was completely converted after just 5 h of reaction. Recycling  experiments indicates that in CH3CN, activity of catalyst recycling decreased significantly in fist recycle. On the other hand, in  CH3COOC2H5 as solvent, no loss of the catalytic activity was observed after at least 2 catalytic cycles of the phenethyalcohol oxidation. In the presence of both NHPI and sec-phenethyl alcohol in CH3CN, the quantity of Co leached is very high. On the contrary, in CH3COOC2H5, the leaching of Co is neglisible in any cases.